Action research / Siti Mariam Mohammad Iliyas - Mohammad Iliyas, Siti Mariam (Faculty of Information Management, 2015)
This article presents about the problems and challenges faced by teachers in their teaching. The problems could be overcome by practicing certain approaches which is related to action research. Also included in this article are steps in implementing action research, types of action research, reasons of doing action research and misconceptions in the understanding of such practice.